Stability of Rosmarinic Acid and Flavonoid Glycosides in Liquid Forms of Herbal Medicinal Products-A Preliminary Study - Agnieszka Bodalska; Adam Kowalczyk; Izabela Fecka (MDPI AG, 2021)
Peppermint leaf, sage leaf, thyme herb, and their preparations are common components of herbal medicinal products (HMPs). According to the European Pharmacopoeia guidelines, the above-mentioned plant substances are standardized for the content of essential oils, omitting polyphenols, which also have a significant impact on their activities. The aim of this study was to evaluate the stability of the predominant polyphenols-rosmarinic acid, luteolin-7-O-β-glucuronide, and eriocitrin-in selected commercial liquid HMPs containing thyme, sage, and peppermint under long-term, intermediate, and accelerated testing conditions. Qualitative and quantitative analyses of these polyphenols were performed by the previously optimized and validated HPLC-DAD method. Rosmarinic acid stability was better in hydroethanolic than in an aqueous solution. The effect of the solvent on the stability of luteolin-7-O-β-glucuronide and eriocitrin could not be determined and requires further investigation. The present study is the first to analyze the stability of these compounds in commercial herbal medicinal products. The expiration dates proposed by the manufacturers of the tested HMPs did not guarantee stable levels of all analyzed polyphenols throughout the stated period. However, this study is preliminary and requires continuation on a larger number of medicinal products.